Effect of Red Bull energy drink on muscle performance: an electromyographic overview - Pai, K. M.; Kamath, A.; Goel, V. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The present study was aimed at investigating the effect of Red Bull Energy drink (RB) on muscle endurance and fatigue.